Investigation of oral problems using a novel oral symptom assessment tool in patients with advanced cancer and older patients with frailty. - Cleary, Niamh Mairéad (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2024)
Oral symptoms are common in patients with advanced cancer. Certain oral symptoms like xerostomia are common in older patients. The prevalence of many oral symptoms is however unknown in older patients with frailty. Oral symptoms/ problems are a direct and indirect cause of morbidity in both patient groups. A symptom assessment tool helps to capture how a patient is experiencing a symptom. The Oral Symptom Assessment Scale (OSAS) is a novel 20-item oral symptom assessment tool. We conducted two prospective observational studies with the OSAS as the central theme. The aim of the first study was to carry out further testing of the psychometric properties of the original OSAS, with the objectives being to assess its reliability, and to further assess its criterion validity using a cancer-related oral quality of life instrument (the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire – Oral Health 15 /EORTC QLQ-OH15). 51 completed tests were obtained. The study data suggested at least moderate agreement between analogous questions on the OSAS and the EORTC QLQ-OH15. The test-retest results for the presence of symptoms were good, with one symptom having “almost perfect” agreement, 12 symptoms having “substantial” agreement, and six symptoms having “moderate” agreement. The focus of the second study was to investigate the prevalence and clinical features of oral symptoms using a slightly modified version of the OSAS (the symptom of ‘drooling’ was added based on investigator experience) in a cohort of older patients with frailty. Data from the first 100 participants recruited was reported. The results suggest that many oral symptoms are common (and of high impact) in older patients with frailty. Xerostomia (57%) and drooling (40%) were the most common reported symptoms. The preliminary findings provide a novel insight into the prevalence and clinical features of oral symptoms not previously investigated using a multi-dimensional symptom-specific assessment tool.
APPROVED
Keywords: oral care; oral health; palliative care; neoplasms; symptom assessment; frailty